Reavaliação do Patrimônio - de Castro, Antônio Alves; Marquito, Marcelo Mázala; Godinho, Luiz Carlos; Rocha, Marcos Ribeiro; Coutinho, Paulo Roberto da Silva; Rodrigues, Heleno (Contabilidade Vista & Revista, 2009)
O artigo não possui resumo.